Higher incidence of Zika in adult women than adult men in Rio de Janeiro suggests a significant contribution of sexual transmission from men to women - Flavio Codeço Coelho (International Journal of Infectious Diseases, 2016)
Objectives: The recent emergence of Zika in Brazil and its association with an increased rate of congenital malformations has raised concerns over its impact on the birth rate in the country. Using data on the incidence of Zika in 2015–2016 and dengue in 2013 and 2015–2016 for the city of Rio de Janeiro (population 6.4 million), a massive increase of Zika in women compared to men was documented. Methods: The age-adjusted incidence was compared between men and women. A negative binomial Poisson generalized linear model was fitted to the Zika incidence data to determine the significance of sexual transmission statistically. Results: Even after correcting for the bias due to the systematic testing of pregnant women for Zika, there were found to be 90% more registered cases per 100 000 women than men in the sexually active age group (15–65 years); this was not the case for age groups <15 years and >65 years. Assuming that infected men transmit the disease to women in their semen, but that the converse is not true, some extra incidence in women is to be expected. An alternate hypothesis would be that women visit doctors more often than men. To test this, the incidence of dengue fever was compared in men and women in 2015 and in 2013 (before Zika reached Rio de Janeiro): in both years, women were 30% more likely to be reported with dengue. Conclusion: Women in the sexually active age group are far more likely to get Zika than men (+90% increase); sexual transmission is the most probable cause. Women in the 15–65 years age group are also 30% more likely to be reported with dengue than men, which is probably due to women being more careful with their health.